Optimasi Kesesuaian Alat Gali-Muat dengan Alat Angkut untuk Mengatur Fuel Ratio dalam Menghemat Pemakaian Fuel pada Pengupasan Overburden di Pit Jebak 1 PT. Nan Riang Kabupaten Batanghari Provinsi Jambi - Januardi Putra; Tamrin Kasim (Journals Mining Engineering : Bina Tambang, 2018)
Abstrak. PT. Nan Riang is a coal mining company located in Kecamatan Muara Tembesi, Kabupaten Batanghari, Provinsi Jambi. The overburden daily production target is 2.500 bcm / day, while the actual production is 2.310,91 bcm / day. One of the factors that have not been achieved is the composition of excavators and dump truck that have not been optimal, each fleet uses 1 excavator and 2 dump truck. The excavator used for overburden stripping activities is Volvo EC460BLC and Komatsu PC400LC, while for the transport equipment used is the A40E Articulated Dump Truck. Based on observations in the field using these combinations results in a waiting time on the digging equipment. This has an impact on April's fuel use of 153.389 liters and in May 111.051 liters exceeded the specified target of 100.000 liters / month. Based on calculations with the composition of 1 excavator and 2 dump truck, the actual match factor value on fleet 1 is 0,519 and fleet 2 is 0,462, while the ideal match factor value is 1. The actual fuel ratio obtained is 0,723 liters / bcm and 0,905 liter / bcm and the fuel consumption of both fleet is 196,17 liters / hour, with the actual fuel cost of Rp. 689.747.769,91 / month. After optimization, it was found that the ideal composition for overburden stripping was 1 excavator and 4 dump truck carried out with 1 fleet, the excavator used was Volvo EC460BLC. With this composition obtained productivity of 2.503,65 bcm / day, with a match factor value of 1,03 and the obtained fuel ratio of 0,590 liters / bcm and fuel consumption obtained at 155.58 liters / hour. By using this composition spend a fuel cost of Rp. 547.045.478,60 / month. Then we get savings of Rp. 142.702.291,31 / month. If the savings in the form of diesel fuel are 11.566,92 liters.  Keywords : Match Factor, Fuel Ratio, Fuel Consumption, Fuel Cost,  Productivity.